THE OPTIMIZATION OF TWO-WHEELED MOTOR BIKE PATROLS IN PREVENTING THE AGGRAVATED ACTS OF BURGLARY IN THE LEGAL AREA OF RESORT POLICE OF BREBES (POLRES BREBES) - Harris Islamy Pasya Harris (Police Studies Review, 2022)
The increasing cases of burglary is causing public disturbance. Polres Brebes, in this case Samapta as a preventive act through routine police patrol is highly responsible to solve this problem. The objective of this review paper is to discuss solution methods that can be used to solve and identify the factors which affects the effectiveness of the patrol and describing the effort of increasing the role of Two Wheels Vehicle Patrol Unit in prevention of the burglary cases in Polres Brebes. The theory and concept which is conducted in this research are Samapta Patrol Unit, patrol, patrol management, also the factors that affects the patrol according to Management theory, burglary, and crime prevention. This research uses qualitative approach while using the participant observation field research method. The data is collected through interview, observation, and document studies, also the data validity using data triangulation. The research shows that burglary cases is still high in number based on Polres Brebes crime index. The role of Two Wheels Police Patrol by Samapta in the act of prevention towards burglary has not been optimal for it still has many deficiency in every stage of the patrol management based on Perkabaharkam Number 1 Year 2017 and Management theory, six main factor of management exists and also inhibitors in each reality of the patrol. Through this research we can conclude that evaluation and optimization is needed to solve main problems including the balancing of personnel through Daftar Satuan Personel (DSP), the need of patrol development training, the upgrading of existing police patrol, and the mapping of burglary crime hotspot.